Enhancing ERP Performance and Business Efficiency Through TOGAF Implementation - Andika Isma; Andi Naila Quin Azisah Alisyahbana (Indonesian Journal of Enterprise Architecture, 2024)
This article discusses how TOGAF (The Open Group Architecture Framework) is applied to Gojek's corporate information system with the aim of increasing business efficiency and information system performance. In the growing digital era, information systems are very important for business. TOGAF helps companies develop, plan, implement, and properly manage their architecture. In this article, the basic concepts of TOGAF are explained, as well as how Gojek companies can implement them. This study used a qualitative method by conducting interviews with Gojek and Enterprise Resource Planning (ERP) employees. In addition, the results and discussion of the GAP analysis conducted on Gojek's business architecture, data architecture, and enterprise application architecture are discussed in this article. TOGAF is expected to improve the performance of Gojek's information system. This article provides an overview of the topics to be covered and summarizes the contents of the article.